A Igreja Local como Igreja inculturada - Miranda, Mário de França (Revista eclesiástica brasileira, 2001)
. This paper attempts to emphasise the importance of the Local Church — understood in a wider sense — for the full experience of the faith. First it points to the Church's anthropological dimension, a comununity for those that take in and experience the faith, but always in a given socio-cultural context. Respectfor cultural diversity permits a rich variety of expressions and practices of the same faith, and makes possible a dynamic catholicity. The Church is then able to carry out in a more efficient manner its mission of being a sacrament of Jesus Christ's salvation. In the final session the author applies this insight to the reality of the Church in Brazil.